Design of A Circular Ring Monopole Antenna with Inverted T‐Strip Line for Dual‐Band Operation. Issue 9 (27th June 2013) - Seo, Yongseok; Lee, Hyeonjin; Lim, Yeongseog
ABSTRACT A novel and simple design of a coplanar waveguide‐fed multiband antenna formed by a circular ring monopole antenna is investigated for DCS/PCS/UMTS/LTE_CN/WLAN. The impedance bandwidths that were achieved reach to about 0.84 GHz (1.68–2.52 GHz) 42.0% at the center frequency of 2.0 and 0.72 GHz (5.14–5.86 GHz) 13.1% at the center frequency of 5.5 GHz. Moreover, the resonant characteristics of the antenna can be tuned by using the inverted T‐strip line. Experimental results exhibit that the proposed circular ring antenna creates a monopole‐like pattern in the E‐plane and an omnidirectional radiation pattern in the H‐plane, so it is well suitable to meet DCS/PCS/UMTS/LTE_ CN/WLAN operations. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2174–2176, 2013